2021
DOI: 10.1186/s12894-021-00882-9
|View full text |Cite
|
Sign up to set email alerts
|

Cross-organ sensitization between the prostate and bladder in an experimental rat model of lipopolysaccharide (LPS)-induced chronic pelvic pain syndrome

Abstract: Background The aim of the current study was to investigate the effects of chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) on bladder function via prostate-to-bladder cross-sensitization in a rat model of lipopolysaccharide (LPS)-induced prostate inflammation. Methods Male rats were intraprostatically injected with LPS or saline, serving as control. Micturition parameters were examined in a metabolic cage 10 or 14 days later. Subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…48 giving rise to bladder overactivity and alterations in both afferent and efferent signaling. 49 A recent study in a rat experimental model highlights a crucial role of calcitonin gene related peptide signaling as a significant driver of visceral pain and, in particular, abdominopelvic pain associated with the bladder and colon. 50 At a neuronal level, cross-sensitization between gut and prostate is defined as a result of afferent signaling from the LUT and distal intestine via various central and peripheral neural mechanisms.…”
Section: Anatomical Peculiarities Of Pelvic Region and Cross-organ Se...mentioning
confidence: 99%
See 1 more Smart Citation
“…48 giving rise to bladder overactivity and alterations in both afferent and efferent signaling. 49 A recent study in a rat experimental model highlights a crucial role of calcitonin gene related peptide signaling as a significant driver of visceral pain and, in particular, abdominopelvic pain associated with the bladder and colon. 50 At a neuronal level, cross-sensitization between gut and prostate is defined as a result of afferent signaling from the LUT and distal intestine via various central and peripheral neural mechanisms.…”
Section: Anatomical Peculiarities Of Pelvic Region and Cross-organ Se...mentioning
confidence: 99%
“…Histopathological analysis demonstrated prostatic inflammation in CP/CPPS animals. This suggested that prostate‐to‐bladder cross‐sensitization can be triggered by an infectious focus in the prostate, giving rise to bladder overactivity and alterations in both afferent and efferent signaling 49 …”
Section: Pathophysiology Of the Gut‐prostate Axismentioning
confidence: 99%